PERLINDUNGAN HUKUM TERHADAP KORBAN TINDAK PIDANA KEKERASAN PADA ANAK DITINJAU DARI UNDANG-UNDANG NO. 35 TAHUN 2014 TENTANG PERLINDUNGAN TERHADAP ANAK DI PEKANBARU - Arianti, Novia Sukma; Arafat, Zain Alwi (Fakultas Hukum dan Sosial Universitas Sunan Giri Surabaya, 2023)
Children are descendants that Allah SWT has entrusted to us to be cared for and protected, because in them there are rights, dignity and human dignity that must be upheld. Children are weak and helpless creatures who need love and attention. However, in practice in society, there are not a few children who do not get the proper attention from their families and surroundings. Along with the times, the state through the government has made various efforts to provide the best for children. Violence against children continues to occur. In Indonesia, in particular, various cases of violence against children have appeared in various regions. A surprising fact is that a child in Malang was splashed with hot water by his own mother. The reason is quite trivial, the child often defecates anywhere and makes the mother angry. At the end of October 2022, the public was shocked by the tragic incident in Pekanbaru because a biological mother and stepfather tortured and lit a 10-year-old boy's genitals with cigarettes.